Inspiring the Ecological Mission of the American Catholic Church: Laudato Si’ at a Moment of Crisis and Hope - Erin Lothes Biviano (Journal of Moral Theology, 2020)
This article was delivered on June 28, 2019 as the first plenary address at the inaugural gathering of “_Laudato Si_’ in the United States: A Conference Series on Our Common Home” co-sponsored by Creighton University and Catholic Climate Covenant. Erin Biviano Lothes outlines the spirituality and relational theological anthropology of _Laudato Si’_. Rooted in this foundation, she then constructs a framework for Catholic energy ethics and diagnoses “gaps” that account for insufficient faith-based action on climate change in the US. Lothes then emphasizes climate change communication theory as critical to adequate climate action and suggests individual and collective actions, especially around impact investing, that persons and communities of faith can take to sufficiently address the climate crisis.